Polymer Photovoltaic Cell Using TiO2/G-PEDOT Nanocomplex Film as Electrode - F. X. Xie; C. J. Liang; Z. Q. He; Y. L. Tao (International Journal of Photoenergy)
Using TiO2/G-PEDOT (PEDOT/PSS doped with glycerol) nanocomplex film as a substitute for metal electrode in organic photovoltaic cell is described. Indium tin oxide (ITO) worked as cathode and TiO2/G-PEDOT nanocomplex works as anode. The thickness of TiO2 layer in nanocomplex greatly affects the act of this nonmetallic electrode of the device. To enhance its performance, this inverted organic photovoltaic cell uses another TiO2 layer as electron selective layer contacted to ITO coated glass substrates. All films made by solution processing techniques are coated on the transparent substrate (glass) with a conducting film ITO. The efficiency of this solar cell is compared with the conventional device using Al as electrode.